Strategi Implementasi Metode Tilawati di TPQ Al Fath Trowangsan - Hafidah Faris Al Falaq; Hakimuddin Salim (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
The purpose of this study is to describe the implementation strategies of the Tilawati method in Quranic education in Trowangsan Village. The Tilawati method is a Quranic teaching method that utilizes intonation (rost) and combines classroom-based and individual instruction to improve the ability to recite the Quran with proper pronunciation (tartil). This study employs a descriptive qualitative approach with a field research design. The research subjects include teachers and students at TPQ Alfath. The research object is the Quran learning process using the Tilawati method. Data collection techniques include observation and interviews, while data analysis involves the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the method is carried out through three stages: the opening, the main activity, and the closing activity. The strategies employed include practical learning, the use of the rost tone, the classical method, and the individual method through the Simak approach. The use of these methods has proven effective in enhancing students’ engagement, motivation, and fluency in reading the Quran, particularly in understanding the length of recitation and the rules of tajwid. Additionally, the learning process supports the use of digital media as a tool for independent learning. Thus, the Tilawati method is considered effective and relevant for teaching Quranic recitation at the elementary education level, as it fosters an interactive and enjoyable learning process.